Successful pregnancy in an end-stage renal disease woman on chronic hemodialysis - Fatemeh Yaghoubi; Farnaz Tavakoli; Davood Dalil; Saeid Iranzadeh (Society of Diabetic Nephropathy Prevention, 2022)
Successful conception in a female patient on hemodialysis (HD) is considered a high-risk pregnancy and associated with maternal and fetal complications. Thus, most such pregnancies lead to abortion or termination to preserve maternal health. Here, we report a successfully-delivered case of a 19th-week-diagnosed pregnancy in a 35-year-old mother with end-stage renal disease (ESRD). We present the case of a 35-year-old female with ESRD, diagnosed 10 years ago secondary to glomerulonephritis. The patient underwent the deceased-donor renal transplantation once, which unfortunately was rejected. During the initial tests for second-time kidney transplantation, a human chorionic gonadotropin-beta (beta-hCG) positive with a level of 9953 mIU/mL was reported, suggesting the pregnancy. The transvaginal ultrasonography confirmed the pregnancy at an approximate gestational age of 19 weeks. As a result, the patient underwent four and half hours of intensive HD five times a week and continued until 36 weeks of pregnancy. At 36 weeks, the patient presented to Shariati hospital, Tehran, Iran, with low- back pain. Consequently, a cesarean section (C/S) was performed, and the baby boy was born with a nine of ten Apgar score. Although successful pregnancy is possible for women with ESRD, it requires special multidisciplinary care. Intensive HD and regular fetal monitoring have improved the pregnancy outcome in this population. However, the risk of severe complications is still for the health of the mother and her offspring.